Zone of genetic instability in polyploide hybrid spined loaches (Cypriniformes, Cobitidae, Cobitis) in the Middle Dnieper - Mezhzherin, S.V.; Tsyba, A.A.; Saliy, T.V.; Lutcenko, D.S. (Reports of the National Academy of Sciences of Ukraine, 2019)
As a result of a screening study of the spined loach populations of the hybrid group Cobitis elongatoides — taenia — tanaitica of Ukrainian water systems, the cases of mass anomalies of allozyme spectra of polyploids specimens characterized by clone reproducing were revealed. Anomalies occur locally and were found only in populations of the two right tributaries of the upper part of the Middle Dnieper (the Irpen River and the upper part of the Teteriv River system). This narrow region should be considered as a zone of genetic instability. Obviously, the anomalies have a mutational nature, since they are stably manifested in a number of generations. They can be classified into five types. The cause for their appearance should be considered chemical pollution. This situation of mass genetic abnormalities is unique and has not been observed anywhere before. Thus, surface water pollu tion in Ukraine in some regions has reached a critical level and leads to obvious genotoxic effects.